An integral duality formula - Grecu, Bogdan C.; Ryan, Raymond A. (MATHEMATICA SCANDINAVICA, 2006)
We establish an integral formula for the duality between multilinear forms/homogeneous polynomials and tensor products for dual spaces with the approximation property and for which the injective tensor products of their preduals is separable and does not contain a copy of _1. We deduce some multilinear Bishop-Phelps-type results.